STUDI TINGKAT KEMANDIRIAN PASIEN STROKE DI RUANG UNIT STROKE RSUD DR. SOEDOMO TRENGGALEK - Awan, Awan Hariyanto (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2025)
Stroke can cause mobility disorders or motor disorders, visual disturbances, speech disorders, emotional changes, and other symptoms according to the location of the brain that is blocked. Motor deficits in stroke patients can affect independence in carrying out daily activities and cause patients to experience self-care deficits or dependence on others who require continuous nursing assistance in carrying out daily activities. The purpose of this study was to identify the level of independence of stroke patients in the Stroke Unit Room of Dr. Soedomo Trenggalek Hospital. The research design used was quantitative descriptive. The population in the study was 42 stroke patients with a sample size of 29 respondents. The sampling technique used purposive sampling. Data analysis in this study used a frequency distribution in the form of a percentage. The results showed that the independence of stroke patients from 29 patients while being treated in the hospital experienced dependence in carrying out daily activities, namely 2 respondents (7%) experienced total dependence, 7 respondents (24%) experienced severe dependence, 7 respondents (24%) experienced moderate dependence, and 13 patients (45%) experienced mild dependence. The conclusion of the study showed that stroke patients experienced impaired independence dependence that must be assisted in carrying out daily activities.